Penggunaan Daun Lamtoro Sebagai Pakan Untuk Penggemukan Sapi Bali - Syamsul Hidayat Dilaga; Muhamad Amin; Oscar Yanuarianto; Sofyan Sofyan; Dahlanuddin Dahlanuddin (Universitas Mataram, 2021)
Farmers are not used to giving leucaena leaves to the cattle they keep. This is because lack of information about benefits of leucaena is not widely known. Whereas leucaena leaves have high nutritional value and palatable. Cattle body weight can grow well, so farmers get an advantage when using leucaena as feed.Extension activity was conducted in Kelompok Tani Ternak Aik Kolong, Mura Village, District of Brang Ene, West Sumbawa Regency. Selection of places at the request of community leaders from this place. After the extension activities, farmers have begun to understand and realize that the maintenance cattle for fattening efforts absolutely need quality feed intake. Farmers will seed and a plant leucaena seed given in the cage area, yard, or in their fields after the rainy season arrives. This was conveyed in discussions (Q&A) events that developed during extension activities and technical guidance conducted in a simulation. In the end of activities, the farmers still hope that this kind of activity is more often done, so that their skills and knowledge on how to raise cattle fattening can be applied in the Group in particular and in Mura Village-Brang Ene, West Sumbawa Regency generally.